Fossil fishes and anurans from the Miocene of Rio Chico and Cerro Zeballos, Chubut province, Argentina - Agnolin, Federico (2021)
The fossil record of freshwater fishes and anurans from the Miocene in Patagonia is relatively patchy, a large number of specimens remaining undescribed. The aim of the present contribution is to describe a fossil association of percomorphacean fishes and calyptocephalellid anurans from the early to late Miocene Collón Curá Formation, at Chubut province, Patagonia, Argentina. In spite of being represented by several specimens, both anurans and fishes show a very low taxonomic diversity. This pattern matches with other fossil sites from the Cenozoic of Patagonia, as well as with the extant Patagonian batrachofaunas and ichthyofaunas. The fossil record of frogs and fishes in Patagonia is represented by few lineages that have a large evolutionary history in the area, and occasionally can be traced up to the Late Mesozoic.